Numerical Modeling of Soil Evaporation Process and Its Stages Dividing during a Drying Cycle - Jiangbo Han; Jin Lin; Yunfeng Dai (Geofluids)
The soil water evaporation is a critical component of both the surface energy balance and water balance, affecting the mass and energy exchange between the land and the atmosphere. Evaporation process is involved in the highly complex interactions between media properties, transport processes, and boundary conditions. So, it is difficult to accurately determine these near-surface highly dynamic processes based only on the sparse field data and on the measurement-based methods. The objective of this paper was to obtain a detailed description of the soil water evaporation process and to better understand the evolutions of variables involved in the evaporation process during different stages of evaporation. To do this, a numerical simulation experiment in a bare silt soil was conducted to reproduce the soil drying process during a 20-d period after a 2-cm rainfall event. According to simulation results, the whole 20-d simulation period was divided into two main stages as well as a transient period from stage 1 to stage 2. Diurnal patterns of energy and water balance components, soil moisture, soil temperature, water fluxes, evaporation rate, dry surface layer (DSL), and evaporation zone during this drying process were fully described, which, in turn, could be as the possible indicators for judging the shift of stages of evaporation.